2003
DOI: 10.1007/s000180300050
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant anti-P protein autoantibodies isolated from a human autoimmune library: reactivity, specificity and epitope recognition

Abstract: The ribosomal P proteins are specific and important autoantigens in patients affected by systemic lupus erythematosus. In this study, we describe for the first time the selection and characterization of recombinant human monoclonal anti-P protein (auto)-antibody fragments from an autoimmune patient-derived phage display antibody library. The selected recombinant anti-P antibodies specifically recognize the P proteins in immunofluorescence assays on HEp-2 cells and in immunoblotting assays, and they immunopreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…An average to high level of mutation was identified in S3A8 and M4H1 V H clones, indicative of an antigen-driven response. Similar observations have been reported for other autoantibodies [24,26,37], though the previously described Ro52 specific IgM monoclonals contained no mutations and two replacements together with two silent mutations, respectively [38].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An average to high level of mutation was identified in S3A8 and M4H1 V H clones, indicative of an antigen-driven response. Similar observations have been reported for other autoantibodies [24,26,37], though the previously described Ro52 specific IgM monoclonals contained no mutations and two replacements together with two silent mutations, respectively [38].…”
Section: Discussionsupporting
confidence: 80%
“…Selections were performed with (a) a library derived from SLE patient S339, and (b) a mix of the five libraries derived from autoimmune patients diagnosed with MCTD, SLE and UCTD (Mix) [24].…”
Section: Phage Libraries and Selection Proceduresmentioning
confidence: 99%
“…Thus, the ribosomal stalk is directly involved in the translocation step of protein synthesis [9]. It has been previously shown that antibodies against the C-terminal region of ribosomal P proteins (markers of systemic lupus erythematosus in humans) and their scFv recombinant forms posses the ability to block in vitro translation in a rabbit reticulocyte lysate system [10], [11]. In chronic Chagas' heart disease, antibodies against the C-terminal region of T. cruzi ribosomal P proteins have been also detected [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune patient libraries of SLE (patients D5, D18, D181, O11, and Z5), systemic sclerosis (SSc) (patients B92, H248, J70, S185, and T5), and rheumatoid arthritis (RA) (patients Du, He, and Wy) patients were available in pHenIX-VSV vector format (23)(24)(25). The synthetic library made by Nissim et al (26) was used for test selections.…”
Section: Phage Display Libraries and Patient Seramentioning
confidence: 99%
“…Libraries of RA, SSc, and SLE patients (23)(24)(25) were mixed using equal amounts of phages from each library, and phages…”
Section: Test Selections On Biotinylated Cytoplasmicmentioning
confidence: 99%